Surveillance improves survival of patients with hepatocellular carcinoma: a prospective population‐based study. Issue 8 (24th September 2018) - Hong, Thai P; Gow, Paul J; Fink, Michael; Dev, Anouk; Roberts, Stuart K; Nicoll, Amanda; Lubel, John S; Kronborg, Ian; Arachchi, Niranjan; Ryan, Marno; Kemp, William W; Knight, Virginia; et al.
Abstract: Objectives: To determine the factors associated with survival of patients with hepatocellular carcinoma (HCC) and the effect of HCC surveillance on survival. Design, setting and participants: Prospective population‐based cohort study of patients newly diagnosed with HCC in seven tertiary hospitals in Melbourne, 1 July 2012 – 30 June 2013. Main outcome measures: Overall survival (maximum follow‐up, 24 months); factors associated with HCC surveillance participation and survival. Results: 272 people were diagnosed with incident HCC during the study period; the most common risk factors were hepatitis C virus infection (41%), alcohol‐related liver disease (39%), and hepatitis B virus infection (22%). Only 40% of patients participated in HCC surveillance at the time of diagnosis; participation was significantly higher among patients with smaller median tumour size (participants, 2.8 cm; non‐participants, 6.0 cm; P < 0.001) and earlier Barcelona Clinic Liver Cancer (BCLC) stage disease (A/B, 59%; C/D, 25%; P < 0.001). Participation was higher among patients with compensated cirrhosis or hepatitis C infections; it was lower among those with alcohol‐related liver disease or decompensated liver disease. Median overall survival time was 20.8 months; mean survival time was 18.1 months (95% CI, 16.6–19.6 months). Participation in HCC surveillance was associated with significantly lower mortality (adjusted hazard ratio [aHR], 0.60; 95% CI, 0.38–0.93; P = 0.021), as were curative therapies (aHR, 0.33; 95% CI, 0.19–0.58). Conversely, higher Child–Pugh class, alpha‐fetoprotein levels over 400 kU/L, and later BCLC disease stages were each associated with higher mortality. Conclusions: Survival for patients with HCC is poor, but may be improved by surveillance, associated with the identification of earlier stage tumours, enabling curative therapies to be initiated.